Diagnostic vale of serum NSE, and s-100β and inflammatory markers levels in epilepsy : Diagnostic vale of serum NSE, and s-100β - Li, Zhaoxia; Su, Li; Lu, Yi; Hu, Yunqing; Yang, Qian (Journal of Medical Biochemistry, 2025)
Aim:To sodium valproate lore the effects of sodium valproate on serum inflammatory factors and s-100β levels in patients with emergency secondary epilepsy(SE). Methods:This was a retrospective cohort of 120 patients with SE who received Sodium valproate that compared with a group who received carbamazepine regarding different therapeutic drugs. The general data, interleukin (IL)-2, IL-8, tumor necrosis factor (TNF)-α, neuron-specific enolase (NSE), serum acid calcium-binding protein s-100β, total effective rate(TER), seizure onset condition, and adverse reactions (Ars) of the two groups were compared at baseline and at 3 months later. Results:There were no significant differences in age, gender, BMI, course of the disease, stroke type, or seizure type between the study groups (P>0.05). The results showed that IL-2 of the Sodium valproate group (53.17±4.95 µg/L) was lower versus Carbamazepine group (62.38±4.83 µg/L) (P<0.05). The IL-8 of the Sodium valproate grouppostoperatively (26.48 ± 2.73 µg/L) was lower versus Carbamazepine group (33.54±3.39 µg/L) (P<0.05). Postoperatively, the TNF-αin Sodium valproate group (32.18±4.26 µg/L) was lower versus the Carbamazepine group (41.03±4.92 µg/L) (P<0.05). The s-100β (0.29±0.15) µg/L in the Sodium valproate group was lower versus Carbamazepine group (0.54±0.14) µg/L (P<0.05). The TER of the Sodium valproate group (93.33%) was higher versus the Carbamazepine group of 75% (P<0.05). The number of epileptic seizures 0.81±0.08 times per year in the Sodium valproate group was versus 1.23±0.12 times per year in the Carbamazepine group. The duration of epilepsy in the Sodium valproate group (2.53±0.22 min/time) was shorter than that in the Carbamazepine group (3.08±0.24 min/time). Conclusion: sodium valproate can drastically relieve the epileptic symptoms of patients with SE, and there was no great difference in ARs. Hence, it is safe and worthy of popularization and application.